Deep Capillary Plexus Features in Acute Macular Neuroretinopathy - Cabral, Diogo (2022)
Purpose: The purpose of this study was to identify a precise location of deep capillary plexus (DCP) injury in acute macular neuroretinopathy (AMN) lesions using multimodal imaging. Methods: En face structural optical coherence tomography (OCT) images were manually segmented to delineate outer retinal AMN lesions involving the ellipsoid zone and interdigitation zone. AMN lesion centroid was calculated, and image distortion was applied to correct for Henle fiber layer (HFL) length and orientation. The resulting image was registered with the corresponding en face OCT angiography (OCTA) image segmented at the DCP and structural OCT volume before grading for vascular and structural features, respectively. Results: Thirty-nine AMN lesions from 16 eyes (11 female patients, mean age 34 ± 4 years) were analyzed. After correcting for HFL anatomy, in 62% of AMN lesions, the centroid co-localized with a capillary vortex (pattern 1); flow defects were detected in 33% of lesions (pattern 2); and in 5% of lesions no specific pattern could be identified (pattern 3). The detection of a specific pattern increased after correcting the projection of AMN lesion for HFL anatomy (28% vs. 5%, P = 0.04). Outer nuclear layer thickness was lower in the centroid area in 10 (29%) AMN lesions from 6 patients, all corresponding to lesions fitting pattern 2 (r = 0.78, P < 0.001). Conclusions: AMN lesions might be a result of DCP impairment at the level of the capillary vortex or draining venule. In eyes with AMN, the location of outer retinal changes associated with DCP ischemia appears to be influenced by the length and orientation of HFL.